The Influence of E-Wallets on Student Lifestyle - Dian Eka Zahra; Aliska Putri Simatupang; Fildzah Zaira . Br . Hsb; Nazrah Anggraini; Shasyabilla Umaya Nasution (Outline Publisher, 2026)
This study aims to analyze the influence of e-wallet usage on the lifestyle of students in Class B of the Economics Department at Universitas Negeri Medan. The research is grounded in the rapid development of digital technology, which has driven the transformation of financial transactions toward cashless systems. The method used is qualitative descriptive, with data collected through questionnaires. The results show that e-wallets facilitate daily transactions, improve efficiency, and support a practical and digital lifestyle. However, this convenience also contributes to an increase in consumptive behavior, such as impulsive shopping and a tendency toward overspending. Although most students perceive e-wallets as a symbol of modernity, concerns remain regarding data security and technical issues. These findings suggest that e-wallet usage should be balanced with strong financial literacy to maximize its benefits while minimizing negative impacts on students' consumption patterns and financial management.